Repply to: Brito, A.C., Brotas, V., Caetano, M., Coutinho, T.P., Bordalo, A.A., Icely, J., Neto, J.M., Serôdio, J., Moita, T. (2012) "Defining phytoplankton class boundaries in Portuguese transitional waters: an evaluation of the ecological quality status according to the Water Framework Directive" [Ecological Indicators 19, 5-14] - Domingues, Rita B. (2012)
We write to comment on the recently published paper “Defining phytoplankton class boundaries in Portuguese transitional waters: an evaluation of the ecological quality status according to the Water Framework Directive” (Brito et al., 2012). This paper presents an integrated methodology to analyse the ecological quality status of several Portuguese transitional waters, using phytoplanktonrelated metrics. One of the systems analysed, the Guadiana estuary in southern Portugal, is considered the most problematic estuary, with its upstream water bodies classified as Poor in terms of ecological status. We strongly disagree with this conclusion and we would like to raise awareness to some methodological constraints that, in our opinion, are the basis of such deceptive conclusions and should therefore not be neglected when using phytoplankton to assess the ecological status of natural waters.